The Implementation of Village Government Administration in Improving Public Services in Singkep Village, Lingga Regency, Riau Islands - Juita Siti Rahayu; Timbul Dompak (Penerbit Jurnal Indonesia, 2024)
One of the driving forces behind village government is the apparatus.The village government's apparatus serves as executor administration and provides services to community members who are service objects.The purpose of this study is to ascertain how well the apparatus functions in executing administrative duties and providing community services at the village level. The purpose of this study is to ascertain how village government in SINGKEP VILLAGE, LINGGA REGENCY, contributes to community service quality improvement.This study employs a qualitative descriptive approach that focuses on the village government's role in enhancing the community's access to administrative services in SINGKEP VILLAGE, LINGGA REGENCY.The findings demonstrated that the Tangible dimension, Reliability, Responsiviness, Assurance, and Empathy, as well as their respective indicators, had been incorporated into the quality of administrative services in SINGKEP VILLAGE, LINGGA REGENCY.However, there are still some indicators that are not meeting the community's expectations. These indicators include the inconvenience of the service location, which includes facilities and infrastructure that are incomplete, employees who have not utilized SOPs (Standard Operational Procedures) effectively, and employees who are still unfriendly in the service process.